Metal halide vapor lasers with halide production inside the gas discharge tube; XVIII International Symposium on Gas Flow and Chemical Lasers & High-Power Laser 2010, August 30th−September 3rd, 2010, Sofia, Bulgaria - Gubarev F. A. Fedor Aleksandrovich; Evtushenko G. S. Gennady Sergeevich; Sukhanov V. B. Viktor Borisovich; Shiyanov D. V. Dmitry Valeryevich (2009, 2009)
В фонде НТБ ТПУ отсутствует